Preoperative chemoradiotherapy for oesophageal cancer: a systematic review and meta-analysis. Issue 7 (11th June 2004) - Fiorica, F; Di Bona, D; Schepis, F; Licata, A; Shahied, L; Venturi, A; Falchi, A M; Craxì, A; Cammà, C
Abstract : Background: The benefit of neoadjuvant chemoradiotherapy in oesophageal cancer has been extensively studied but data on survival are still equivocal. Objective: To assess the effectiveness of chemoradiotherapy followed by surgery in the reduction of mortality in patients with resectable oesophageal cancer. Methods: Computerised bibliographic searches of MEDLINE and CANCERLIT (1970–2002) were supplemented with hand searches of reference lists. Study selection: Studies were included if they were randomised controlled trials (RCTs) comparing preoperative chemoradiotherapy plus surgery with surgery alone, and if they included patients with resectable histologically proven oesophageal cancer without metastatic disease. Six eligible RCTs were identified and included in the meta-analysis. Data extraction: Data on study populations, interventions, and outcomes were extracted from each RCT according to the intention to treat method by three independent observers and combined using the DerSimonian and Laird method. Results: Chemoradiotherapy plus surgery compared with surgery alone significantly reduced the three year mortality rate (odds ratio (OR) 0.53 (95% confidence interval (CI) 0.31–0.93); p = 0.03) (number needed to treat = 10). Pathological examination showed that preoperative chemoradiotherapy downstaged the tumour (that is, less advanced stage at pathological examination at the time of surgery) compared with surgery alone (OR 0.43 (95% CI 0.26–0.72); p = 0.001). The risk for postoperative mortality was higher in the chemoradiotherapy plus surgery group (OR 2.10 (95% CI 1.18–3.73); p = 0.01). Conclusions: In patients with resectable oesophageal cancer, chemoradiotherapy plus surgery significantly reduces three year mortality compared with surgery alone. However, postoperative mortality was significantly increased by neoadjuvant chemoradiotherapy. Further large scale multicentre RCTs may prove useful to substantiate the benefit on overall survival.